Microendoscopic Removal of Deep-Seated Brain Tumors Using Tubular Retraction System - Ratre, Shailendra; Yadav, Yad Ram; Parihar, Vijay Singh; Kher, Yatin (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2016)
Background Retraction of the overlying brain can be difficult without causing significant trauma when using traditional brain retractors with blades. These retractors may produce focal pressure and may result in brain contusion or infarction. Tubular retractors offer the advantage of low retracting pressure that is less likely to be traumatic. Low retraction pressure in the tubular retractor is due to the distribution of retraction force in all directions in a larger area.Material and Methods We conducted a retrospective study of 100 patients with deep-seated tumors operated on from January 2010 to December 2014. Tumor removal was accomplished with the help of a microscope and/or endoscope. Tubular brain retractors sizes 23, 18, and 15 mm were used. Folding of the tubular retractor after making a longitudinal cut allowed a small corticectomy. Larger retractor sizes were used in the earlier part of the study and in larger tumors. All the patients were evaluated postoperatively by computed tomography scan on the first postoperative day, and subsequent scans were done as and when needed. Any brain contusion or infarctions and the amount of tumor removal were recorded.Results A total of 74 patients had astrocytomas; 12, meningiomas; 4, colloid cyst of the third ventricle; 4, metastases; 4, primitive neuroectodermal tumor; 1, neurocytoma; and 1, ependymoma. Pure endoscopic excision without using a microscope was performed in 12 patients. Lesions were in the frontal (n = 34), parietal (n = 22), intraventricular (n = 16), basal ganglion or thalamic (n = 14), occipital (n = 10), and cerebellar (n = 4) areas. Total, near-total, and partial excision was achieved in 49, 29, and 22 patients, respectively. Use of a conventional retractor for excision of peripheral and superficial parts of a large tumor, small brain contusions, and technical failure were observed in 7, 4, and 1 patient, respectively. The low incidence of contusion may be partly due to the nonavailability of magnetic resonance imaging in the early postoperative period because of financial constraints.Conclusion Removal of deep-seated tumors was safe and effective using our simple tubular retractor. It also helped minimize bleeding during surgery. A tubular brain retractor and conventional retractor can be used to complement each other if required.
Keywords: brain retractors; brain tumors; minimally invasive surgical procedures; neuroendoscopy; tubular retractor system